Konseling Islam Berbasis Akhlaq Karimah dalam Transformasi NPD: Implementasi Tazkiyah Al-Nafs sebagai Pendekatan Terapeutik - Abdul Karim; Ahmad Syamsul Muarif (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
This research is motivated by the phenomenon of increasing Narcissistic Personality Disorder (NPD) in the digital era that encourages self-obsession and narcissistic behavior, while secular Western therapeutic approaches have not fully aligned with the spiritual values ​​of the Muslim community. The main objective of this research is to develop an Islamic counseling model based on akhlaq karimah (good character) in transforming NPD through the tazkiyah al-nafs approach. The method used is a qualitative research with an instrumental case study design, with participants being six students and alumni of the Darussalam Blokagung Islamic Boarding School aged 18-35 years who have NPD characteristics based on the NPI-16. Data were collected through semi-structured in-depth interviews, participant observation for 3-4 months, and document analysis, then analyzed using thematic analysis with an inductive-deductive approach. The results of the study show four main themes of transformation: decreasing narcissistic characteristics through spiritual awareness, increasing akhlaq karimah (good character), the strategic role of Islamic boarding school spiritual guidance, and the dynamics of the tazkiyah al-nafs process which includes the stages of takhalli, tahalli, muhasabah, and tajalli. These findings indicate that Islamic counseling based on noble character is effective in systematically and sustainably transforming egocentric orientations toward theocentric ones. Based on these results, this study concludes that the Islamic counseling model using the tazkiyah al-nafs framework is capable of producing deeper and more meaningful personality transformation than conventional approaches. The implications of this research are expected to provide an alternative, culturally appropriate therapeutic approach for the Muslim community and enrich the development of an evidence-based, contemporary Islamic psychological framework.